The effect of internal focus and external focus instruction in improving novices overhand volleyball serve / Fatin Aqilah Abdul Razak - Abdul Razak, Fatin Aqilah (2013)
An explicit instruction is needed in performing a task. Instructions that focusing more on the coordination of the body is complex to be followed comparing to instruction focusing on equipments or effects of environment. Purpose of the study was to determine the outcome of specific instruction to novices of Uitm Shah Alams’ Kesatria. A total of hundred thirty two participated the study which age ranged 20-25 years old. Participants were randomly divided to three different groups. Instruction referred to group A was internal focus instruction (body coordination) whilst group B received external focus instruction (the effect of environment or apparatus) and control group received no focus instruction .A North Carolina University Volleyball Battery Test was adopted for the assessment of serving score. Instruction was assessed by using overhand volleyball serve scoring. Total of 6 blocks of 5 trials were performed during acquisition phase and 1 block of 5 trials were performed on retention phase. A one way repeated measure ANOVA was conducted to determine the differences between internal and external focus instruction groups in relation to acquisition and retention phase. Result from Post Hoc with Bonferroni correction confirmed that external focus instruction group shown most significant difference (p<0.05) in instruction scoring. In serving scoring, external focus instruction was significant difference (p<.0.05). Data yielded significant difference on external group on the instruction and serving scoring in acquisition and retention phase with (p < 0.05). Findings, the result has made a significant on the effectiveness of specific instruction to the novices. The study shown that external focus instruction group performed better in acquisition and retention phase.